The Racial Discrimination Reflected In Frances Patton Statham's Trail Of Tears (1993): A Sociological Approach - Nugroho, David Eko, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
The major problem of this study is how the racial discrimination is reflected in Trail of Tears novel. The objectives of this study are to analyze the novel based on its structural elements and to describe the racial discrimination in the novel based on the sociological analysis. The object of the study is Trail of Tears novel by Frances Patton Statham. In analyzing Trail of Tears novel, the writer uses qualitative method and sociological approach. The data source consists of primary data and secondary data sources. The primary data source is Trail of Tears novel and the secondary data sources are the other sources related to the analysis such as books of literary theory, the author's biography and the other relevant information. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, based on its structural analysis, Frances Patton Statham through this novel wants to show the racial discrimination of the whites towards American Indians. Second, based on the sociological analysis, the novel is closely related to the social phenomena of America in the late twentieth century, in which there are disparities between American Indians and the whites.